Adenosine Attenuates Human Coronary Artery Smooth Muscle Cell Proliferation by Inhibiting Multiple Signaling Pathways That Converge on Cyclin D. Issue 6 (December 2015) - Dubey, Raghvendra K.; Fingerle, Jürgen; Gillespie, Delbert G.; Mi, Zaichuan; Rosselli, Marinella; Imthurn, Bruno; Jackson, Edwin K.
Abstract : The goal of this study was to determine whether and how adenosine affects the proliferation of human coronary artery smooth muscle cells (HCASMCs). In HCASMCs, 2-chloroadenosine (stable adenosine analogue), but not N 6 -cyclopentyladenosine, CGS21680, or N 6 -(3-iodobenzyl)-adenosine-5′- N -methyluronamide, inhibited HCASMC proliferation (A2B receptor profile). 2-Chloroadenosine increased cAMP, reduced phosphorylation (activation) of ERK and Akt (protein kinases known to increase cyclin D expression and activity, respectively), and reduced levels of cyclin D1 (cyclin that promotes cell-cycle progression in G1). Moreover, 2-chloroadenosine inhibited expression of S-phase kinase–associated protein-2 (Skp2; promotes proteolysis of p27 Kip1 ) and upregulated levels of p27 Kip1 (cell-cycle regulator that impairs cyclin D function). 2-Chloroadenosine also inhibited signaling downstream of cyclin D, including hyperphosphorylation of retinoblastoma protein and expression of cyclin A (S phase cyclin). Knockdown of A2B receptors prevented the effects of 2-chloroadenosine on ERK1/2, Akt, Skp2, p27 Kip1, cyclin D1, cyclin A, and proliferation. Likewise, inhibition of adenylyl cyclase and protein kinase A abrogated 2-chloroadenosine's inhibitory effects on Skp2 and stimulatory effects on p27 Kip1 and rescued HCASMCs from 2-chloroadenosine–mediated inhibition. Knockdown of p27 Kip1 also reversed the inhibitory effects of 2-chloroadenosine on HCASMC proliferation. In vivo, peri-arterial (rat carotid artery) 2-chloroadenosine (20 μmol/L for 7 days) downregulated vascular expression of Skp2, upregulated vascular expression of p27 Kip1, and reduced neointima hyperplasia by 71% ( P <0.05; neointimal thickness: control, 37 424±18 371 pixels; treated, 10 352±2824 pixels). In conclusion, the adenosine/A2B receptor/cAMP/protein kinase A axis inhibits HCASMC proliferation by blocking multiple signaling pathways (ERK1/2, Akt, and Skp2) that converge at cyclin D, a key G1 cyclin that controls cell-cycle progression. Abstract : Supplemental Digital Content is available in the text.